Peranan, Peluang dan Kendala Pengembangan Agroindustri di Indonesia - nFN Supriyati; Erma Suryani (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2006)
EnglishThis article aimed to assessing the dynamics of the role of agroindustry, as well as assessing the threat and opportunity of the agroindustry development in Indonesia. Agroindustry was developed since mid of 1970’s. In the period of 1985-2000, the share of agroindustry in GDP increased from 3.7 percent to 12.73 percent. In the meantime, the role of agroindustry in labor absorption increased within the range of 0.2 percent to 8.53 percent. The increase in added value was not followed by the increase in labor absorption. Added value mostly came from large-scale industries which was relatively stagnant in the period of 1974-2003. About 90 percent the total home industries could only create around 6 percent of added value. This fact shows a huge gap between large-scale and small-scale/home industries. Opportunity to develop agroindustry is remain open, taking into account the availability of the raw materials and the increasing demand of the processed products. Agroindustry has a significant backward and forward linkages compared to the other sectors. The agroindustry development constraints, among others, are: (1) Assurance of quality and continuity of agricultural products; (2) Relatively poor human resources capacity; (3) Simple technology instead of modern technology used by most of the producers; and (4) Lack in partnership development among the large/medium-scale agroindustries and small-scale/home agroindustries.IndonesianTulisan ini bertujuan untuk menelaah dinamika peranan agroindustri, serta kendala dan peluang pengembangannya di Indonesia. Agroindustri mulai dikembangkan sejak pertengahan tahun 1970an. Dalam periode 1985-2000, peranan agroindustri dalam penciptaan PDB meningkat dari 3,7 persen menjadi 12,73 persen. Sementara itu, peranan agroindustri dalam penyerapan tenaga kerja meningkat dari 0,2 persen pada tahun 1985 menjadi 8,53 persen. Namun demikian, peningkatan peranan dalam penciptaan nilai tambah tidak diikuti oleh peningkatan penyerapan tenaga kerja. Peranan dalam penciptaan nilai tambah, sebagian besar berasal dari industri skala besar, dan tidak terjadi pergeseran yang signifikan dalam periode tahun 1974-2003. Sementara itu, industri rumah tangga yang jumlahnya sekitar 90 persen hanya mampu menciptakan nilai tambah sekitar 6 persen. Hal ini menunjukkan adanya ketimpangan yang sangat besar antara industri skala besar dan skala rumah tangga. Peluang pengembangan agroindustri masih terbuka, baik ditinjau dari ketersediaan bahan baku maupun dari sisi permintaan produk olahan. Disamping itu, agroindustri mempunyai keterkaitan ke belakang dan ke depan yang kuat dengan sektor lainnya. Kendala-kendala dalam pengembangan agroindustri, antara lain: (1) kualitas dan kontinyuitas produk pertanian kurang terjamin; (2) kemampuan SDM masih terbatas; (3) teknologi yang digunakan sebagian besar masih bersifat sederhana, sehingga menghasilkan produk yang berkualitas rendah; dan (4) belum berkembang secara luas kemitraan antara agroindustri skala besar/sedang dengan agroindustri skala kecil/rumah tangga.